Equation of state of fluid aluminum in the metal–nonmetal transition region. (28th June 2018) - Rakhel, A D
Abstract: A phenomenological equation of state is constructed for fluid aluminum to study thermodynamic consequences of the metal–nonmetal transition occurring in the fluid on the thermal expansion. It is demonstrated that the existing experimental data clearly indicate the isochores plotted in the internal energy-pressure plane are straight lines. Based on this fact and some general thermodynamic relations it is shown that the equation of state must have the Mie–Grüneisen–Debye form in this case. This means that such concepts as the cold curve, the Grüneisen coefficient, and the Debye temperature can be applied to the fluid state. In order to demonstrate the accuracy of the present equation of state these characteristics as functions of the molar volume have been determined and compared with the dependencies used in the literature. Considering the fluid as a system constituted of the valence electrons and ions and applying the virial theorem, the dependence of the kinetic energy of the electronic subsystem on temperature and the molar volume has been determined. Using the above dependence a thermodynamic criterion has been derived for the metal–nonmetal transition which is governed by the thermal expansion.